Peran Kelompok Usaha Dalam Digital Marketing dan Inovasi Produk untuk Meningkatkan Kesejahteraan dan Kemandirian Ekonomi Masyarakat Desa Kanugrahan: Peran Kelompok Usaha Dalam Digital Marketing dan Inovasi Produk untuk Meningkatkan Kesejahteraan dan Kemandirian Ekonomi Masyarakat Desa Kanugrahan - Walidatul Amiyah (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
The purpose of this literature study discussion is to describe the role of MSME business groups in improving welfare and economic independence in digital marketing and product innovation in Kanugrahan Village. The research method used is a qualitative research method using a descriptive approach. The focus of the research is on business groups in Kanugrahan Village. This business was chosen because it has been proven to be able to face anything, including monitoring crises, and has a large role in generating income and improving the welfae of society.